2011
DOI: 10.3389/fphys.2011.00016
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of Neural Stem Cells

Abstract: Embryonic cortical neural stem cells are self-renewing progenitors that can differentiate into neurons and glia. We generated neurospheres from the developing cerebral cortex using a mouse genetic model that allows for lineage selection and found that the self-renewing neural stem cells are restricted to Sox2 expressing cells. Under normal conditions, embryonic cortical neurospheres are heterogeneous with regard to Sox2 expression and contain astrocytes, neural stem cells, and neural progenitor cells sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 53 publications
0
33
0
2
Order By: Relevance
“…The Wnt, BMP, and FGF signaling pathways that show well-established and characterized roles in NCC formation in avians, fish, and amphibians appear to be required primarily for lineage specification of NCCs in mammalian embryos. It is important to note that as neural stem cells differentiate into NCCs, there is a clear switch in Sox expression state with Sox2 being inactivated in concert with the activation of Sox9 and then Sox10 in progenitors and migrating NCCs, respectively (Remboutsika et al 2011). These parameters may present avenues for ultimately identifying the key signals required for mammalian NCC formation, which will provide insights into the evolution of neural crest cells and their properties as well as facilitate ways to generate neural crest cells from hESCs and iPS cells, both of which will be enormously beneficial in the application of NCCs to tissue engineering and regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt, BMP, and FGF signaling pathways that show well-established and characterized roles in NCC formation in avians, fish, and amphibians appear to be required primarily for lineage specification of NCCs in mammalian embryos. It is important to note that as neural stem cells differentiate into NCCs, there is a clear switch in Sox expression state with Sox2 being inactivated in concert with the activation of Sox9 and then Sox10 in progenitors and migrating NCCs, respectively (Remboutsika et al 2011). These parameters may present avenues for ultimately identifying the key signals required for mammalian NCC formation, which will provide insights into the evolution of neural crest cells and their properties as well as facilitate ways to generate neural crest cells from hESCs and iPS cells, both of which will be enormously beneficial in the application of NCCs to tissue engineering and regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In further support of this idea, the transient nature of NCC induction and migration from primitive neuroepithelium, led to the assumption that it would be unlikely for NC precursor cells to persist during the major period of neuroepithelial maturation and central nervous system (CNS) development. However, a very recent study demonstrated that NCCs can indeed still be generated from the cortex of E14.5 embryos and that this capacity depends primarily on the inactivation of Sox2 and the activation of Sox9 [17]. Moreover, following transplantion into the hindbrain of chick embryos, cortical neurosphere-derived NCCs recapitulate endogenous NCC migratory pathways colonizing the proximo-distal extent of the pharyngeal arches and differentiating into sensory neurons within the cranial ganglia.…”
Section: The Multipotency Of Nccs: the Classical Workmentioning
confidence: 99%
“…Moreover, following transplantion into the hindbrain of chick embryos, cortical neurosphere-derived NCCs recapitulate endogenous NCC migratory pathways colonizing the proximo-distal extent of the pharyngeal arches and differentiating into sensory neurons within the cranial ganglia. This provocatively implies that the developmental segregation of the CNS and NC and thus NSCs and NCCs may be reversible even over extended periods of time [17].…”
Section: The Multipotency Of Nccs: the Classical Workmentioning
confidence: 99%
“…Accordingly, several researchers have transplanted astrocytes or astrocyte precursors into the site of SCI to encourage regeneration (Hasegawa et al, 2005; Davies et al, 2006; Filous et al, 2010; Jin et al, 2011). However, with increasing evidence of glial heterogeneity and plasticity (Meletis et al, 2008; Davies et al, 2008; White et al, 2010; Remboutsika et al, 2011) we propose that an attractive alternative strategy is to target the endogenous astrocyte response and stimulate the formation of growth-permissive cellular bridges to support growing axons.…”
Section: Introductionmentioning
confidence: 99%